2016
DOI: 10.1007/s12036-016-9411-z
|View full text |Cite
|
Sign up to set email alerts
|

From Nearby Low Luminosity AGN to High Redshift Radio Galaxies: Science Interests with Square Kilometre Array

Abstract: We present detailed science cases that a large fraction of the Indian AGN community is interested in pursuing with the upcoming Square Kilometre Array (SKA). These interests range from understanding low luminosity active galactic nuclei in the nearby Universe to powerful radio galaxies at high redshifts. Important unresolved science questions in AGN physics are discussed. Ongoing low-frequency surveys with the SKA pathfinder telescope GMRT, are highlighted.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 161 publications
(195 reference statements)
0
3
0
Order By: Relevance
“…The key science drivers of the SKA encompass many important areas of research related to AGN physics and the connection between MBHs and galaxies in the context of galaxy formation and evolution. As detailed in numerous recent white papers, the SKA will directly probe jet-ISM feedback through observations of neutral hydrogen absorption against radio jets, constrain radio AGN duty cycles through spectral aging studies, and provide a census of the radio AGN population at low luminosities and high redshifts (Agudo et al 2015;Kapinska et al 2015;Kharb et al 2016;McAlpine et al 2015;Orienti et al 2015;Prandoni & Seymour 2015;Smolcic et al 2015). Thus, there is indeed significant overlap between the scientific questions that the SKA and the ngVLA will address regarding AGNs (see Section 2), but we emphasize that this overlap is synergistic in nature.…”
Section: Skamentioning
confidence: 99%
“…The key science drivers of the SKA encompass many important areas of research related to AGN physics and the connection between MBHs and galaxies in the context of galaxy formation and evolution. As detailed in numerous recent white papers, the SKA will directly probe jet-ISM feedback through observations of neutral hydrogen absorption against radio jets, constrain radio AGN duty cycles through spectral aging studies, and provide a census of the radio AGN population at low luminosities and high redshifts (Agudo et al 2015;Kapinska et al 2015;Kharb et al 2016;McAlpine et al 2015;Orienti et al 2015;Prandoni & Seymour 2015;Smolcic et al 2015). Thus, there is indeed significant overlap between the scientific questions that the SKA and the ngVLA will address regarding AGNs (see Section 2), but we emphasize that this overlap is synergistic in nature.…”
Section: Skamentioning
confidence: 99%
“…An issue in the latter studies is the relatively small fraction of FRI sources found in current all-sky surveys -due to their relatively high detection and completeness threshold, high redshift and/or low luminosity, low-surface brightness source populations are not probed well. Upcoming all-sky surveys with SKA will probe FRI populations to high redshifts (Kapinska et al 2015) and would be able to answer these questions (Kharb et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, optical spectra provided by the WEAVE-LOFAR survey (Smith et al 2016) will be beneficial in identifying LDR2 counterparts to unidentified γ-ray sources. In the long term, surveys with the Square Kilometre Array (SKA) will also be key in studying this population (Kharb et al 2016). This table is available in its entirety in machine-readable form.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%